Penanaman Nilai Karakter Disiplin dan Religius Melalui Pembiasaan Shalat Dhuha di SD Negeri 4 Kancilan Jepara - Melinda Febri Hapsari (Perkumpulan Kualitama Edukatika Indonesia, 2023)
The character of the students at SD Negeri 4 Kancilan before the Duha prayer habituation was not good. This is evidenced by the existence of case records of several students who lack disciplinary and religious character values, such as bullying their friends, refusing to continue school, and not attending school for two weeks without permission. After holding a character education strengthening program through the habit of Duha prayer which has been running for five years, students who originally had poor character values ??became students with fairly good character. Based on this description, this study aims to describe the results of inculcating the values ??of disciplinary and religious character through the habit of praying dhuha at SD Negeri 4 Kancilan Jepara. The method used in this research is descriptive qualitative research method. The instruments used in this study were observation, interviews, questionnaires and documentation. From this study it shows that instilling character education through the habit of praying dhuha at SD Negeri 4 Kancilan can instill discipline and religious character values.